Identification of tourism potential and 3A analysis (attraction, amenity, accessibility) in maitara village of akebay village - Bahtiar Majid; Betly Taghulihi (Journal of Gastro Tourism, 2023)
This research aims to identify tourism potential and analyze 3 A (attraction, accessibility and amenties) in Maitara Village of Akebay Village. It is hoped that from this research the government and the community of Maitara Kampung Akebay Village will get an overview and guidelines on tourism development in Akebay Village. Tourism development certainly requires attractions to be used as tourist attractions, easy access such as roads and transportation and additional supporting facilities such as lodging, restaurants, toilets, and so on which are called the 3 A terms. From the results of field research there are several potentials that can be used as tourist attractions in Maitara Village, Akebay Village including, Nature Tourism, Culture and Fitness Tourism. The theory used is the theory of potential, tourist attraction and 3A. The conclusion of this research is that there are several types of attractions that can be offered by Maitara Kampung Akebay Village as a tourist attraction, namely (1). Nature tourism consisting of Camping Ground, Tracking, (2) Cultural Tourism consists of "Bakerah" and traditional games, (3) Artificial Tourism consists of intagramable photo spots and swimming pools for children.